Evolution of star clusters in time-variable tidal fields - Mamikonyan, Ernest N.; Mac Low, Mordecai-Mark (The astrophysical journal, 2017)
Strong tidal forces can dominate star cluster evolution in merging galaxies, determining their mass-loss rates and lifetimes. In order to model this evolution, we have developed a second-order accurate numerical method for integrating a star cluster in an arbitrary time-variable tidal field. We extend the Kira N -body integrator to handle these external fields. We obtain realistic tidal histories from a galaxy merger simulation including sink particles, which we interpret as young star clusters. Coupling these tidal accelerations to N -body models of isolated clusters, we perform detailed dynamical studies. This generalizes the formalism previously used to explore the dynamical effects of the galactic tidal field on clusters in circular orbits. We find that, in contrast to previous studies that considered only stellar and dark matter dynamics, tidal interactions between clusters and dense gas in the galactic disk can significantly influence cluster mass loss and lifetimes. Using our models, we develop an effective semianalytic model that can be used for fast estimation of cluster mass loss in a galactic tidal field and to study the evolution of the globular cluster mass function in isolated and merging galaxies.